Critérios para adoção de soluções de desenvolvimento multiplataforma móvel na perspectiva de desenvolvedores de software - Afonso, Felipe Munhoz (2020)
Cross-platform Development Tools are a technology that emerged to meetthe demand of development teams that operate simultaneously with more than onemobile platform. This technology mainly benefits small and medium-sized teamsthat did not have the capacity to maintain two or more different code bases for thesame project. The use of these tools has become more and more popular accord-ing to the evolution of the technology employed capable of producing applicationsincreasingly closer to one developed natively. As the popularity of cross-platformtools grows, so does the need for a concise, flexible and long-lasting way of definingtheir advantages and disadvantages over other tools. So the objective of this work isto find out through mixed methods of data gathering such as questionnaires, inter-views and practical studies what really matters to the developers, thus contributingto the evolution of the state of the art by providing a set of criteria that can beused to make comparisons. And enhancing the state of the art with a comparisonbetween the development tools most used today. Results shows that the most im-portant decision factors are Responsivity, Long Term Viability and Maintainability.It was also indentified that the most complete tools are React Native, Flutter andXamarin.